MODEL PENDAMPINGAN BELAJAR ORANG TUA UNTUK ANAK BERKEBUTUHAN KHUSUS SELAMA MASA PANDEMI - Tias Rahmawati; Fartiwi Fartiwi; Umi Nur Fatimah (Academica: Journal of Multidisciplinary Studies, 2020)
Education is a basic right for every citizen, including children with special needs who need guidance from people who are experts in their fields. During the pandemic, children were required to study at home with guidance from their parents. The purpose of this study was to find out the model of parental learning guidance for children with special needs during the pandemic. This research uses a case study method and data collection using interviews with thematic analysis. From the results of the study, there are three models of parent learning guidance for children with special needs during the pandemic, namely learning guidance using permissive, authoritarian, and authoritative parenting approaches.Keywords: children whit special needs; guiding study; pandemic